Pembelajaran Lagu Ngarak Telok Herujo Oleh Band Eksotika pada Kegiatan Ekstrakurikuler di SMK Negeri 1 Tobali - Aprianto, Bambang; Kurniawan, Irfan; Siswanto, Silo (ANTHOR: Education and Learning Journal, 2022)
The purpose of the study was to find out how the learning process again Ngarak Telok Herujo in extracurricular activities at SMK Negeri 1 Toboali. The method used in this research is a qualitative approach. The data collection technique used is triangulation, namely observation, interviews, and documentation. Based on the results of the study, it was found that this learning process occurred in stages consisting of planning, implementation and evaluation. The results of the planning have been described, namely the preparation of schedules, materials, methods and media. The results of the implementation have also been described, namely the application of materials, application of methods. Followed by the overall results, namely evaluation.